Revisitations - Ferguson, Jenanne (My University, 2022)
It is often challenging to find the strands that connect articles in a given issue of a small yet heavily interdisciplinary regional studies journal. Yet I often marvel at how certain themes emerge time and time again. This issue is random at first glance; the topics are individually diverse when compared, but it is mostly their perennially significant nature within our region that makes them similar. Therefore, in this first issue of Sibirica’s twenty-first volume, I found that a theme of revisiting (and rethinking) came to the fore. The four articles included here all revisit key themes in Siberian studies—from human-animal interconnectedness and bear ceremonialism to state-instituted identity categories and urbanization—from fresh perspectives.
Keywords: Siberian studies